Rigid Pavement Engineering of Lake-Musi Rawas Intersection Road Based on 2024 Pavement Design Manual - Nopradego, Rendi; Saloma, Saloma; Usman, Arie Putra (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Roads are one of the important elements to improve community economic facilities and infrastructure based on resources, as well as support regions in overcoming rural and sub-district isolation in Musi Rawas Utara Regency (Muratara). The Simpang Lake - Musi Rawas Boundary Road Section is one of the main connecting sections for the community to go to the plantation location and is a priority area in the plantation area. Considering that this section is a priority road section, planning is needed on the Simpang Lake – Musi Rawas Boundary road section using the 2024 Pavement Design Manual. The planned age of the Simpang Lake - Musi Rawas Boundary road section is 20 years with a CBR value of 7.85% JSKN plan of 64,295.49 units, the length of the road tested is 4,800 km. The results obtained are the design of concrete design with a low traffic category with a concrete slab thickness of 200 mm, a thin concrete thickness of 100 mm, an aggregate foundation layer with a thickness of 150 mm and has a Tie Bar with a transverse joint distance of 4.00 m.